A promoção da accountability pelo Instituto Federal de Educação, Ciência e Tecnologia do Sudeste de Minas Gerais - Bergamini, Leandro Curty (2019)
Technologic, economic, and political changes have fostered transformations in the functions of the State through its role of primacy over decisions related to public management. As the functions of the State change to meet the purposes of new times, management models are aligned with these new demands. Therefore, public organizations have been charged, either by the government (legislation) or by society (social control), so that their actions are disclosed in a transparent way and with a constant concern to attend to the wishes and needs of society within the mission of the institution. The present study has as its theme accountability, observed through elements of information transparency, accountability of managers and accountability of public agents, and proposes to verify their promotion in the Federal Institute of Education, Science and Technology of the Southeast of Minas Gerais - IF Sudeste MG. This research is descriptive and exploratory, characterized by a case study with a mixed approach (qualitative and quantitative). Nowadays, current legislation in Brazil clearly proposes the way to implement accountability to public organizations, but it is still seen as a way to be followed. The research showed that in the IF Sudeste MG, regarding the elements that form accountability, it has to be an improvement, as in the information transparency aspect there is still a lack of standardized procedures that allow the society to observe the information, specifically related to Budget Execution; regarding procedures related to accountability, even if this institution is multicampi, and decentralized, it has been verified that they occur according to the legislation recommended; on the aspect of the accountability of the public agents, it was observed that there is a dissonance related to the legislation, particularly in the deadlines of the disciplinary administrative processes; It is concluded that, in the Institution, the mechanisms used for the promotion of accountability are already, in a certain way, institutionalized, but they need to be improved, standardized and expanded, so that their implementation takes place in a complete and homogeneous manner.